The Scent Of Roses - Adithi Rao (India Penguin Random House, 2024)
When Abu disappears one night, Bram Bram Chok comes to live inside Sajad$1 (Bs heart, making him hop in anger and stomp to its tunes. Does Sajad want him to stay? Can anything make him go away?s
Keywords: Realistic Fiction -- Realistic Fiction